Assessment of maize biomass digestibility: Roles of plant age and ensilage duration in biogas generation - Naveen Yadav; Gunda Mohanakrishna; Jyoti Yadav; Radhika Gandu; Rivka Cahan; Smita S. Kumar; Bharath Gandu (Journal of Environmental Chemical Engineering, 2026)

Chronic Fluoride Exposure Disrupts Calcium-Dependent Neurodevelopmental Signalling and Brain Proteomic Architecture: Multi-Target Modulation by Naringin - Ravindra Shantakumar Swamy; Shalini Choudhary; Abhishek Ambawatiya; Vishal Chhabra; Mayank Mishra; Md Abubakar; Smita Shenoy; Naveen Kumar; Rahul L. Gajbhiye; Amita Rai; Velayutham Ravichandiran; Nitesh Kumar (Biological Trace Element Research, 2026)

Integrating Molecular Pathology, Tumor Microenvironment, and Novel Therapies to Overcome Resistance in Glioblastoma - Smita Kumari; Jyotsna Misra; Karthikeyan Ravi; Naveen Kumar; Niraj Kumar Jha; Rohan Gupta (Journal of Molecular Neuroscience, 2026)

FIH dose selection beyond MABEL: Optimizing phase 1 clinical trial starting dose whilst protecting patient safety - Mineo Matsumoto; J. Ryan Polli; Suresh Kumar Swaminathan; Kaushik Datta; Cris Kamperschroer; Marie C. Fortin; Smita Salian-Mehta; Rutwij Dave; Zheng Yang; Payal Arora; Masanori Hiura; Mizuho Suzuki; et al. (Regulatory Toxicology and Pharmacology, 2026)

Assessment of Water Supply and Demand in a Watershed with Climate Change Impacts on Potential Adaptation Strategies - Smita Jaiswal; Susama Sudhishri; Jyoti Patil; Man Singh; Anchal Dass; Khajanchi Lal; Anil K. Mishra; Prashant Singh; Love Kumar; Pankaj Malkani (Agricultural Research, 2026)

Performance assessment of sulfate-reducing bacterial consortium for the treatment of real landfill leachate under anaerobic conditions - Kajal Saini; Anjali Prajapati; Smita S. Kumar; Vivek Kumar; Somvir Bajar (Journal of Environmental Management, 2026)

Nitrosamines in Pharmaceuticals and the Environment: Genotoxic Impurities, Detection Strategies, and Developmental Health Risks - Uday Shashikumar; Hem Nikhilesh Naik; Jayashree E. Veerabhadra; Vimalkumar Krishnamoorthi; Pei-Chien Tsai; Po-Chin Huang; Yi-Hsun Chen; Smita Jauhari; Yuan-Chung Lin; Vinoth Kumar Ponnusamy; Gopalakrishnan Kumar (Current Pollution Reports, 2026)

A Review on the Fate of Emerging Contaminants in Landfill Leachate: Insights from Conventional Treatment Approaches - Kajal Saini; Anjali Prajapati; Smita S. Kumar; Vivek Kumar; Somvir Bajar (Water, Air, & Soil Pollution, 2026)

Mechanistic insights into the antidiarrheal action of phlorizin: modulation of TLR4/NF-κB, PI3K/AKT, and HIF-1 signalling with antispasmodic and antimicrobial effects - Ravi Kushwah; Smita Jain; Meenal Sahu; Chinchu Praisthy LJ; Siddharth Maurya; Taufik Ansari; Mansi; Ashwini Kumar Mishra; Aleksey Kuznetsov (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Computational prediction of cyclotides from Viola odorata as potential inhibitors against the neuraminidase of Streptococcus pneumoniae - Sreejanani Sankar; Ajaya Kumar Sahoo; Shanmuga Priya Baskaran; R. Babu; Smita Srivastava; Areejit Samal (Molecular Diversity, 2026)

Mucoadhesive Polymeric Nanoparticles of Fexofenadine Hydrochloride for Ocular Delivery: Formulation, Characterisation, and Enhanced Permeation Studies - Pallavi Sarkar; Madhuri Desavathu; Smita Jain; Ashwini Kumar Mishra; Ravi Sankara Reddy; Pankaj Kumar Sah (Journal of Pharmaceutical Innovation, 2026)

Integration of medical genetics and genomics into faculty development programs in india: assessment of success and experience of genetic research centre - Shaini Joseph; Neha Minde; Shiny Babu; Harshvardhan Gawde; Chinna Naik; Venkanna Bhanothu; DVS Sudhakar; Juili Bharankar; Tanvi Agarbattiwala; Amisha Kumar; Geetanjali Sachdeva; Smita D. Mahale; et al. (Journal of Community Genetics, 2026)

Naringin alleviates fluoride-induced neurodevelopmental disorders by modulation of SIRT1, autophagy, mitochondrial fission, and ROS generation - Vishal Chhabra; Ravindra Shantakumar Swamy; Annem Ravi Teja Reddy; Rashmi Bhushan; Smita Shenoy; Shreya Maiti; Abubakar; Sarasa Meenakshi; Krishna Murti; Nitesh Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The Tale of the Guanosine Tract in Repeat Expansion Disorders - Smita Karati; Saurabh Rawat; Aditi Pramod Kumari; Soumalya Das; Sakshi Shukla; Amit Kumar (Molecular Neurobiology, 2026)

Unraveling senescence in cancer: mechanistic complexities and therapeutic opportunities - Prajakta Tiwari; Shreesh Kumar Shukla; Smita Rastogi Verma (Molecular Biology Reports, 2025)

Deciphering the Neurotoxic Burden of Micro- and Nanoplastics: From Multi-model Experimental Evidence to Therapeutic Innovation - Smita Kumari; M. Yasmin Begum; Chingakham Chinglenthoiba; Khadga Raj Aran; Siva Parsad Panda; Mosleh Mohammad Abomughaid; Sorabh Lakhanpal; D. Avinash; Niraj Kumar Jha; Rohan Gupta (Molecular Neurobiology, 2025)

Deciphering pathological and population dynamics in Tilletia indica of Karnal bunt of wheat - Sangale Smita; Malkhan Singh Gurjar; Tej Pratap Jitendra Kumar; Jitender Kumar; Poulami Basak; Natasha Kashyap; Rahul Patidar; Muthyala Mahendra; Sri Ananth Kurella; Kartiki Sharma; Sundeep Kumar; Mahender Singh Saharan (Indian Phytopathology, 2025)

Oral Melatonin for Pain Relief During Venepuncture in Neonates– a Pilot Randomized Control Trial - Sushree Smita Behura; Santosh Kumar Panda; Subhrajyoti Tripathy; Ipsa Kujur; Swaranjika Sahoo; Deepti Damayanty Pradhan (European Journal of Clinical Pharmacology, 2025)

Comprehensive polyphenolic profiling, antioxidant, antimicrobial, and cytotoxicity studies of Rhynchostylis retusa (L.) Blume: a medicinal orchid - Anjna Kumari; Rishabh Kaundal; Smita Kapoor; Subhash Kumar; Dharam Singh; Yogesh Kumar Walia; Dinesh Kumar (Natural Product Research, 2025)

Enhanced biodegradation of ibuprofen using bacterial consortia isolated from landfill leachate - Kajal Saini; Smita S. Kumar; Vivek Kumar; Somvir Bajar (Environmental Monitoring and Assessment, 2025)

Genome sequence of Bipolaris maydis inciting maydis leaf blight provides insights into genome architecture and putative effector repertoire - Poulami Basak; Malkhan Singh Gurjar; Tej Pratap Jitender Kumar; Natasha Kashyap; Sri Ananth Kurella; Muthyala Mahendra; Rahul Patidar; Sangale Smita; Kartiki Sharma; Robin Gogoi (Physiological and Molecular Plant Pathology, 2025)

GC–MS profiling and computational analysis of Balanites aegyptiaca phytoconstituents for antidiabetic activity: insights from network pharmacology and molecular docking - Surendra Kumar Gautam; Rakesh Kumar Paul; Smita Jain; Vipin Kumar; Kaisar Raza (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Spirilloxanthin from Verbesina encelioides Flower Extract has Neuroprotective Benefits in Scopolamine-Induced Memory Impaired Rats that Resemble Alzheimer’s Disease - Vartika Verma; Lavisha Rao; Monika Chaudhary; Smita Jain; Kishore Kumar Pinapati; Abhishek Dey; Swapnil Sharma; Nidhi Srivastava (Molecular Neurobiology, 2025)

Demonstrated role of sulfate-reducing bacterial consortia in anaerobic paracetamol biodegradation - Kajal Saini; Smita S. Kumar; Vivek Kumar; Somvir Bajar (Biodegradation, 2025)

Correction: Tectoridin modulates intertwined molecular pathways in metabolic syndrome: insights from network pharmacology, molecular docking, and in vivo studies - Ashwini Kumar Mishra; Pravat Kumar Sahoo; Rajesh Singh; Smita Jain (Inflammopharmacology, 2025)

Pharmacotherapeutic potential of daidzein: insights into mechanisms and clinical relevance - Chinchu Praisthy LJ; Ravi Kushwah; Sachin Dubey; Vipin Kumar; Smita Jain (Inflammopharmacology, 2025)

Tectoridin modulates intertwined molecular pathways in metabolic syndrome: insights from network pharmacology, molecular docking, and in vivo studies - Ashwini Kumar Mishra; Pravat Kumar Sahoo; Rajesh Singh; Smita Jain (Inflammopharmacology, 2025)

Evaluation of the Sporadic Anti-Alzheimer’s Activity of Purpurin Using In Silico, In Vitro, and In Vivo Approaches - Kajol Rustage; Nitish Rai; Saurabh Kumar Sinha; Juhi Goyal; Pragati Chouhan; Bhuvanesh Baniya; Deepti Dubey; Runjhun Singhal; Pooja Malani; Aaushi Pareek; Malvika Pant; Smita Jain; et al. (Molecular Neurobiology, 2025)

Site suitability of sub-surface dam for environmental sustainability in mountainous watershed using MCDM approach - Sangeeta Kumari; Susama Sudhishri; Man Singh; Dhirendra Kumar Singh; Joydeep Mukherjee; Pramod Kumar; Vijay Kumar Prajapati; Anchal Dass; Kunnampuzhath Gopi Rosin; Smita Jaiswal; Sidhartha Gaddam (Environmental Science and Pollution Research, 2025)

Morpho-cultural variability, pathogenicity and molecular identification of Phytophthora cajani isolates causing blight disease of pigeonpea in India - Raj K. Mishra; Abhishek Bohra; Deepak Kumar; A.K. Parihar; K.K. Hazra; Sonika Pandey; Monika Mishra; Satheesh Naik SJ; Nidhi Kumari; D. Datta; Smita Tiwari; Naimuddin; et al. (Physiological and Molecular Plant Pathology, 2025)

Trends and advances in liposome formulation technology with an emphasis on ensuring safety and quality in food and drug applications - Pawan Prabhakar; Soubhagya Tripathy; Deepak Kumar Verma; Smita Singh; Mamta Thakur; Amit Kumar Singh; Prem Prakash Srivastav; Mamoni Banerjee; Ami R. Patel; Mónica L. Chávez González; Gemilang Lara Utama; José Sandoval-Cortés; et al. (Food Bioscience, 2025)

Efficient Agrobacterium mediated plant regeneration using petiole explants and plant transformation of GUS and Bar gene in Momordica charantia L. plants - Sweta B. Kushwaha; S. Vanchinathan; Smita S. Lele; G. Rama Prashat; Suneha Goswami; Ranjeet Ranjan Kumar; Navita Bansal; Arun Kumar; Shelly Praveen; Nandkumar Kunchge; Jyoti S. Gokhale; T. Vinutha (Journal of Plant Biochemistry and Biotechnology, 2025)

Evaluating TGF-β1 gene expression and promoter polymorphism in cervical cancer progression - Pavan Kumar Poleboyina; Akbar Pasha; S. K. Heena; Sneha Malleswari Poleboyina; Smita C. Pawar (Journal of Molecular Histology, 2025)

Eco-phenological drivers of black gram (Vigna mungo (L) Hepper) productivity in diverse environments and their implications for crop improvement - Ashok K. Parihar; Kali Krishna Hazra; Amrit Lamichaney; Debjyoti Sen Gupta; Anil K. Singh; Jai Dev; Samuel Jaberson; Ajaj A. Lone; S.P. Das; Shayla Bindra; R.K. Panwar; Ashok Kumar; et al. (Field Crops Research, 2025)

Phytophagous probiotic foods: Exploring the intersection of characteristics, quality implications, health benefits, and market dynamics - Alaa Kareem Niamah; Shayma Thyab Gddoa Al-Sahlany; Hussein Katai Abdul-Sada; Pawan Prabhakar; Soubhagya Tripathy; Basant Kumar Dadrwal; Smita Singh; Deepak Kumar Verma; Alok Kumar Gupta; Rakesh Mohan Shukla; Mamta Thakur; Ami R. Patel; et al. (Trends in Food Science & Technology, 2024)

Molecular and immunohistochemical alterations in fluoride-induced neurological impediment in adult rats - Sachindra Kumar; Ravindra Shantakumar Swamy; Rashmi Bhushan; Vishal Chhabra; Smita Shenoy; Krishna Murti; Shubhankar Kumar Singh; Nitesh Kumar (Journal of Trace Elements in Medicine and Biology, 2024)

Role of SIRT1 in Potentially Toxic Trace Elements (Lead, Fluoride, Aluminum and Cadmium) Associated Neurodevelopmental Toxicity - Aqsa Fathima; Newly Bagang; Nitesh Kumar; Somasish Ghosh Dastidar; Smita Shenoy (Biological Trace Element Research, 2024)
The formation of the central nervous system is a meticulously planned and intricate process. Any modification to this process has the potential to disrupt the structure and operation of the brain, which could result in deficiencies in neurological growth. When neurotoxic substances are present during the early stages of development, they can be exceptionally dangerous. Prenatally, the immature brain is extremely vulnerable and is therefore at high risk in pregnant women associated with occupational exposures. Lead, fluoride, aluminum, and cadmium are examples of possibly toxic trace elements that have been identified as an environmental concern in the aetiology of a number of neurological and neurodegenerative illnesses. SIRT1, a member of the sirtuin family has received most attention for its potential neuroprotective properties. SIRT1 is an intriguing therapeutic target since it demonstrates important functions to increase neurogenesis and cellular lifespan by modulating multiple pathways. It promotes axonal extension, neurite growth, and dendritic branching during the development of neurons. Additionally, it contributes to neurogenesis, synaptic plasticity, memory development, and neuroprotection. This review summarizes the possible role of SIRT1 signalling pathway in potentially toxic trace elements -induced neurodevelopmental toxicity, highlighting some molecular pathways such as mitochondrial biogenesis, CREB/BDNF and PGC-1α/NRF1/TFAM.

Hesperidin’s role in the treatment of lung cancer: In-silico and In-vitro findings - Swati Arora; Sumit Sheoran; Bhuvanesh Baniya; Naidu Subbarao; Himanshu Singh; Dhamodharan Prabhu; Neeraj Kumar; Smita C. Pawar; Sugunakar Vuree (In Silico Pharmacology, 2024)

Effect of environmental air pollutants on placental function and pregnancy outcomes: a molecular insight - Sunil Singh; Isha Goel; Smita Tripathi; Ashok Ahirwar; Megha Kumar; Anubhuti Rana; Ruby Dhar; Subhradip Karmakar (Environmental Science and Pollution Research, 2024)

Micropropagation, micromorphological evaluation and genetic homogeneity validation of Cucumis collosus (Rottl.) Cogn.: A wild progenitor of melon - Sumitra Kumari Choudhary; Ashok Kumar Patel; Rekha Chouhan; Kheta Ram; Supriya Ambawat; Smita Shekhawat; Narpat S. Shekhawat (Biocatalysis and Agricultural Biotechnology, 2024)

Multi-location evaluation of field pea in Indian climates: eco-phenological dynamics, crop-environment relationships, and identification of mega-environments - Ashok K. Parihar; Kali Krishna Hazra; Amrit Lamichaney; Debjyoti Sen Gupta; Jitendra Kumar; R. K. Mishra; Anil K. Singh; Anuradha Bhartiya; Parvaze Ahmad Sofi; Ajaz A. Lone; Sankar P. Das; Rajesh Kumar Yadav; et al. (International Journal of Biometeorology, 2024)

A Pilot Study Based on the Correlation Between Whole Exome and Transcriptome Reveals Potent Variants in the Indian Population of Cervical Cancer - Santosh Kumari Duppala; Pavan Kumar Poleboyina; Bhumandeep Kour; Govardhan Bale; Ashish Vyas; Smita C. Pawar; Prashanth N. Suravajhala; Sugunakar Vuree (Indian Journal of Microbiology, 2024)

Evaluating the influence of calcined eggshells and ultrasonication in the Co-digestion of avoidable and unavoidable Food Waste and OLS regression analysis of the reactor system - Taniya Kumari Shaw; Deepak Kumar Rajendran; Smita Raghuvanshi; Sunil Prasad Lohani (Journal of Cleaner Production, 2024)

Pavement distresses monitoring on a stretch of NH-44 (India) using dcnn - Ravi Kumar; Smita Tung (Innovative Infrastructure Solutions, 2024)

Frontier in dark fermentative biohydrogen production from lignocellulosic biomass: Challenges and future prospects - Pushpa Rani; Deepak Kumar Yadav; Arti Yadav; Narsi Ram Bishnoi; Vivek Kumar; Chhotu Ram; Arivalagan Pugazhendhi; Smita S. Kumar (Fuel, 2024)

Anti-obesity potentiality of Lactiplantibacillus plantarum E2_MCCKT isolated from a fermented beverage, haria: a high fat diet-induced obese mice model study - Tridip Kumar Das; Priyanka Kar; Titli Panchali; Amina Khatun; Ananya Dutta; Smita Ghosh; Sudipta Chakrabarti; Shrabani Pradhan; Keshab Chandra Mondal; Kuntal Ghosh (World Journal of Microbiology and Biotechnology, 2024)

Anti-Depressant Like Effects of Aethoscytus Foveolus Oil by Improving Stress-mediated Alterations of Monoamine Oxidase, Oxidative Stress, and Neuroinflammation In-vivo - Lavisha Rao; Vartika Verma; Smita Jain; Kishore Kumar Pinapati; Sameer S. Bhagyawant; Swapnil Sharma; Nidhi Srivastava (Cell Biochemistry and Biophysics, 2024)

Cryptovivipary: A rare phenomenon in monoecious species of Ficus L. (Moraceae) - Smita Debbarma; Biplab Banik; Marami Mili; Dixit Bora; Sani Das; Badal Kumar Datta; Himansu Baijnath (South African Journal of Botany, 2024)

Nanomaterials and biochar mediated remediation of emerging contaminants - Priyadarshani Rajput; Pradeep Kumar; A.K. Priya; Smita Kumari; Seyede Roghie Ghadirnezhad Shiade; Vishnu D. Rajput; Amin Fathi; Arunava Pradhan; Rubab Sarfraz; Svetlana Sushkova; Saglara Mandzhieva; Tatiana Minkina; et al. (Science of The Total Environment, 2024)

Fluoride-Induced Mitochondrial Dysfunction and Approaches for Its Intervention - Sachindra Kumar; Smita Shenoy; Ravindra Shantakumar Swamy; V. Ravichandiran; Nitesh Kumar (Biological Trace Element Research, 2024)

NMR based Serum metabolomics revealed metabolic signatures associated with oxidative stress and mitochondrial damage in brain stroke - Sachin Yadav; Abhai Kumar; Smita Singh; Shahnawaz Ahmad; Gurvinder Singh; Abdul Rahman Khan; Rameshwar Nath Chaurasia; Dinesh Kumar (Metabolic Brain Disease, 2023)

Differential Transcriptional Regulation of Drought Stress Revealed by Comparative RNA-seq Analysis of Contrasting indica Rice from North East India - Smita Sahoo; Kazutaka Kusunoki; Kavita Goswami; Hiroyuki Koyama; Neeti Sanan-Mishra; Sanjib Kumar Panda (Journal of Plant Growth Regulation, 2023)

Assessment of reproductive stage drought tolerance using stress indices in improved restorer lines of KMR-3R in rice - P. Nagaraju; P. Beulah; V. Jaldhani; Y. Manasa; N. Madhusudan; R. M. Sundaram; A. S. Hariprasad; K. Sruthi; M. Sheshu Madhav; Suneetha Kota; M. B. Kalyani; R. Mahender Kumar; et al. (Cereal Research Communications, 2023)

Cost cutting approach of distillery effluent treatment using solar photovoltaic cell driven electrocoagulation: Comparison with conventional electrocoagulation - Smita Badur Karmankar; Alka Sharma; Ranjana Choudhary Ahirwar; Swati Mehra; Dharm Pal; Abhinesh Kumar Prajapati (Journal of Water Process Engineering, 2023)

Habitat characterizations and suitability analysis for conservation implications of Gymnosphaera gigantea (Wall. ex Hook.) S.Y.Dong: a threatened tree fern - Biplab Banik; Stabak Roy; Suman Paul; Muktadhar Reang; Tuhin Das; Koushik Majumdar; Biswajit Baishnab; Dipan Sarma; Smita Debbarma; Saptarshi Mitra; Badal Kumar Datta (Arabian Journal of Geosciences, 2023)

Bonamia semidigyna (Convolvulaceae): a new generic record for Eastern Himalaya region, India - Sani Das; Dixit Bora; Biplab Banik; Aparajita Das; Smita Debbarma; Muktadhar Reang; Panchatapa Bhattacharya; Badal Kumar Datta (Vegetos, 2023)

Phylogenetic and immunological investigations of complete TSA56 ORF of Orientia tsutsugamushi present in acute encephalitis syndrome cases from eastern Uttar Pradesh, India - Pooja Bhardwaj; Sthita Pragnya Behera; Nikita Nanaware; Kamran Zaman; Hirawati Deval; Rajni Kant; Smita Kulkarni; Rajesh Kumar; Gaurav Raj Dwivedi; Rajeev Singh (Archives of Microbiology, 2023)

Landfill leachate valorization: A potential alternative to burden off resources and support energy systems - Smita S. Kumar; Amit Kumar; Sandeep K. Malyan; Pooja Ghosh; Madan Kumar; Rimika Kapoor; Ajay Kumar Agrawal; Sumit Kumar; Vivek Kumar; Lakhveer Singh (Fuel, 2023)

Towards the development of phytoextract based healthy ageing cognitive booster formulation, explored through Caenorhabditis elegans model - Rakesh Pandey; Dayanandan Mani; Karuna Shanker; Dnyaneshwar Umrao Bawankule; Debabrata Chanda; Raj Kishori Lal; Anirban Pal; Puja Khare; Narendra Kumar; Sudeep Tandon; Dharmendra Saikia; Anil Kumar Gupta; et al. (The Nucleus, 2022)

Antihypertensive activity of phytocompounds from selected medicinal plants via inhibition of angiotensin-converting enzyme (ACE) protein: an in-silico approach - Smita Mall; Reetika Srivastava; Nitin Sharma; Chirag N. Patel; Rajan Rolta; Anuradha Sourirajan; Kamal Dev; Arabinda Ghosh; Vikas Kumar (Natural Product Research, 2022)

Unboxing the molecular modalities of mutagens in cancer - Smita Kumari; Sudhanshu Sharma; Dia Advani; Akanksha Khosla; Pravir Kumar; Rashmi K. Ambasta (Environmental Science and Pollution Research, 2022)

Mannose-Anchored Nano-Selenium Loaded Nanostructured Lipid Carriers of Etravirine for Delivery to HIV Reservoirs - Satish Rojekar; Leila Fotooh Abadi; Rohan Pai; Mahendra Kumar Prajapati; Smita Kulkarni; Pradeep R. Vavia (AAPS PharmSciTech, 2022)

Paludisphaera rhizosphaereae sp. nov., a new member of the family Isosphaeraceae, isolated from the rhizosphere soil of Erianthus ravennae - Khongsai L. Lhingjakim; Nandardhane Smita; Gaurav Kumar; Uppada Jagadeeshwari; Shabbir Ahamad; Chintalapati Sasikala; Chintalapati Venkata Ramana (Antonie van Leeuwenhoek, 2022)

Comprehensive technological assessment for different treatment methods of leather tannery wastewater - Mohit Nigam; Puranjan Mishra; Pradeep Kumar; Sunil Rajoriya; Pankaj Pathak; Shraddha Rani Singh; Smita Kumar; Lakhveer Singh (Environmental Science and Pollution Research, 2022)

Immunoreactivity of Brugia malayi Calreticulin and Its Domains with Sera of Different Categories of Bancroftian Filarial Patients - Sunita Yadav; Smita Gupta; Mohd Saeed; Huma Mustafa; Jitendra Kumar Saxena; Puvvada Kalpana Murthy (Acta Parasitologica, 2022)

Identifying critical transitions in complex diseases - Smita Deb; Subhendu Bhandary; Sudipta Kumar Sinha; Mohit Kumar Jolly; Partha Sharathi Dutta (Journal of Biosciences, 2022)

Analysis of thermal effect on propagation of Rayleigh surface waves in a composite structure - Shishir Gupta; Rishi Dwivedi; Smita; Piyush Rai; Sandip Kumar Das (Journal of Earth System Science, 2022)

Genetic diversity among different landraces of Pearl millet [Cenchrus americanus (L.) Morrone syn. Pennisetum glaucum (L.) R. Br.] - Sumitra Kumari Choudhary; Smita Shekhawat; Harish; Meena Barupal; Manoj Kumar; Narpat S. Shekhawat (Vegetos, 2021)

Evaluation of biogas yield and kinetics from the anaerobic co-digestion of cow dung and horse dung: a strategy for sustainable management of livestock manure - Meshach Ileanwa Alfa; Hilary Ijeoma Owamah; Anthony Ogochukwu Onokwai; Sudalaimuthu Gopikumar; Solomon Olakunle Oyebisi; Smita Subodh Kumar; Somvir Bajar; Olusegun David Samuel; Samuel Chukwujindu Ilabor (Energy, Ecology and Environment, 2021)

Secular equation of Rayleigh surface wave in a dry sandy half-space coated by a thin self-reinforced layer - Shishir Gupta; Smita; Snehamoy Pramanik; Arun Kumar Verma (Arabian Journal of Geosciences, 2021)

An elaborative NMR based plasma metabolomics study revealed metabolic derangements in patients with mild cognitive impairment: a study on north Indian population - Umesh Kumar; Abhai Kumar; Smita Singh; Payal Arya; Sandeep Kumar Singh; Rameshwar Nath Chaurasia; Anup Singh; Dinesh Kumar (Metabolic Brain Disease, 2021)

Assessing livelihood-ecosystem interdependencies and natural resource governance in a tribally controlled region of India’s north-eastern middle Himalayas - Mark Everard; Gaurav Kataria; Smita Kumar; Nishikant Gupta (Environment, Development and Sustainability, 2021)
Mountains host high biological and cultural diversity, generating ecosystem services beneficial over multiple geographical scales but suffering significant vulnerabilities. A case study in Lileng village (Arunachal Pradesh, Indian north-east Himalayas) explored linkages between a community with protected tribal rights and the forest and river ecosystems within which they are situated. Evidence was gathered through interviews and literature review about ecosystem service benefits, using the Rapid Assessment of Wetland Ecosystem Services approach. Subsequent analysis using the social, technological, environmental, economic, political framework found close, synergistic relationships between local people and the ecosystems for which they have protected tribal rights. Authoritative local governance arrangements prioritise community subsistence needs, limiting the influence of external state government and private actors on natural resource exploitation. Further sustainable economic development could stem from recognition of the value of ecosystem services produced by intact and functional habitats, and the potential for development of ‘payment for ecosystem services’ markets in addition to ecotourism and cultural tourism. Low food sufficiency and poverty observed in a previous study conducted in Uttarakhand state of the central Indian Middle Himalayas, principal drivers of out-migration and gender/age inequalities, were not evident in Lileng or surrounding areas, apparently linked to tribal rights and authoritative local governance in Arunachal Pradesh leading to greater resource security. Better understanding of ecosystem–community relationships in areas with protected tribal rights can highlight sustainable policies and practices that may be translated into wider geo-political areas, especially in the wake of projected climate change stresses.

Hyperinsulinemia and Hypoadiponectinemia are Associated with Increased Risk for Occurrence of Ovarian Cancer in Non-diabetic Women of North Indian Population - Rohit Kumar Gupta; Sagar Jayantilal Dholariya; Smita Kaushik; S. K. Gupta; Reva Tripathi; Shyam Lata Jain (Indian Journal of Clinical Biochemistry, 2021)

Exogenous trehalose ameliorates methyl viologen induced oxidative stress through regulation of stomatal pore opening and glutathione metabolism in tomato seedlings - Pankaj Borgohain; Bhaben Chowardhara; Bedabrata Saha; Jay Prakash Awasthi; Preetom Regon; Smita Sahoo; Sanjib Kumar Panda (Vegetos, 2020)

Condensation Product of p-anisaldehyde and L-phenylalanine: Fluorescent “on-off” Sensor for Cu2+ and IMPLICATION Logic Gate - Smita Sarma; Bhaswati Devi; Pradip Kr. Bhattacharyya; Diganta Kumar Das (Journal of Fluorescence, 2020)

Arenibacter lacus sp. nov., Isolated from Chilika Lagoon, India - Dhanesh Kumar; Nandardhane Smita; Gaurav Kumar; Gandham Suresh; Uppada Jagadeeshwari; Chintalapati Sasikala; Chintalapati Venkata Ramana (Current Microbiology, 2020)

An early warning system for inundation forecast due to a tropical cyclone along the east coast of India - Anup Kumar Mandal; Ratheesh Ramakrishnan; Smita Pandey; A. D. Rao; Prashant Kumar (Natural Hazards, 2020)

Gene network modules associated with abiotic stress response in tolerant rice genotypes identified by transcriptome meta-analysis - Shuchi Smita; Amit Katiyar; Sangram Keshari Lenka; Monika Dalal; Amish Kumar; Sanjeet Kumar Mahtha; Gitanjali Yadav; Viswanathan Chinnusamy; Dev Mani Pandey; Kailash Chander Bansal (Functional & Integrative Genomics, 2020)

A comparative analysis due to the effect of point source on generation of SH wave - Shishir Gupta; Snehamoy Pramanik; Smita; Arun Kumar Verma (Journal of Earth System Science, 2019)

SlNAC2 overexpression in Arabidopsis results in enhanced abiotic stress tolerance with alteration in glutathione metabolism - Pankaj Borgohain; Bedabrata Saha; Rajkishan Agrahari; Bhaben Chowardhara; Smita Sahoo; Christell van der Vyver; Sanjib Kumar Panda (Protoplasma, 2019)

Cloning of mature pomegranate (Punica granatum) cv. Jalore seedless via in vitro shoot production and ex vitro rooting - Rachana Modi Dinesh; Ashok Kumar Patel; J. B. Vibha; Smita Shekhawat; N. S. Shekhawat (Vegetos, 2019)

Physiological introspection into differential drought tolerance in rice cultivars of North East India - Smita Sahoo; Bedabrata Saha; Jay Prakash Awasthi; Takhellambam Omisun; Pankaj Borgohain; Safiqul Hussain; Jogeswar Panigrahi; Sanjib Kumar Panda (Acta Physiologiae Plantarum, 2019)

Assessing livelihood-ecosystem interdependencies and natural resource governance in Indian villages in the Middle Himalayas - Mark Everard; Nishikant Gupta; Christopher A. Scott; Prakash C. Tiwari; Bhagwati Joshi; Gaurav Kataria; Smita Kumar (Regional Environmental Change, 2019)

Use of water quality index and multivariate statistical techniques for the assessment of spatial variations in water quality of a small river - Smita Dutta; Ajay Dwivedi; M. Suresh Kumar (Environmental Monitoring and Assessment, 2018)

An enhancement of antimicrobial efficacy of biogenic and ceftriaxone-conjugated silver nanoparticles: green approach - Rajasree Shanmuganathan; Davoodbasha MubarakAli; Desika Prabakar; Harshiny Muthukumar; Nooruddin Thajuddin; Smita S. Kumar; Arivalagan Pugazhendhi (Environmental Science and Pollution Research, 2018)

Characterization of phosphate transporter(s) and understanding their role in Leishmania donovani parasite - K.J. Sindhu; Amit Kumar Kureel; Sheetal Saini; Smita Kumari; Pankaj Verma; Ambak Kumar Rai (Acta Parasitologica, 2018)
Inorganic phosphate (Pi) is shown to be involved in excretion of methylglyoxal (MG) in the promastigote form of Leishmania donovani parasite. Absence of Pi leads to its accumulation inside the parasite. Accumulation of MG is toxic to the parasite and utilizes glyoxylase as well as excretory pathways for its detoxification. In addition, Pi is also reported to regulate activities of ectoenzymes and energy metabolism (glucose to pyruvate) etc. Thus, it is known to cumulatively affect the growth of Leishmania parasite. Hence the transporters, which allow the movement of Pi across the membrane, can prove to be a crucial drug target. Therefore, we characterized two phosphate transporters in Leishmania (i) H + dependent myo-inositol transporter (LdPHO84), and (ii) Na + dependent transporter (LdPHO89), based on similar studies done previously on other lower organisms and trypanosomatids. We tried to understand the secondary structure of these two proteins and confirm modulation in their expression with the change in Pi concentration outside. Moreover, their modes of action were also measured in the presence of specific inhibitors (LiF, CCCP). Further analysis on the physiological role of these transporters in various stages of the parasite life cycle needs to be entrenched.

Relative salinity tolerance of rice cultivars native to North East India: a physiological, biochemical and molecular perspective - Takhellambam Omisun; Smita Sahoo; Bedabrata Saha; Sanjib Kumar Panda (Protoplasma, 2018)

Relationship between salt tolerance and nanoparticle synthesis by Williopsis saturnus NCIM 3298 - Pallavi Mohite; Ameeta Ravi Kumar; Smita Zinjarde (World Journal of Microbiology and Biotechnology, 2017)

An improved micropropagation system, ex vitro rooting and validation of genetic homogeneity in wild female Momordica dioica: an underutilized nutraceutical vegetable crop - Sumitra Kumari Choudhary; Ashok Kumar Patel; Harish; Smita Shekhawat; Narpat S. Shekhawat (Physiology and Molecular Biology of Plants, 2017)

Syntrophic association and performance of Clostridium, Desulfovibrio, Aeromonas and Tetrathiobacter as anodic biocatalysts for bioelectricity generation in dual chamber microbial fuel cell - Smita S. Kumar; Sandeep K. Malyan; Suddhasatwa Basu; Narsi R Bishnoi (Environmental Science and Pollution Research, 2017)

Simultaneous Biodegradation of Polyaromatic Hydrocarbons by a Stenotrophomonas sp: Characterization of nid Genes and Effect of Surfactants on Degradation - Smita Kumari; Raj Kumar Regar; Abhay Bajaj; Ratnasekhar Ch; Gubbala Naga Venkata Satyanarayana; Mohana Krishna Reddy Mudiam; Natesan Manickam (Indian Journal of Microbiology, 2017)

Condensation Product of Phenylalanine and Salicylaldehyde: Fluorescent Sensor for Zn2+ - Smita Sarma; Pradip Kr. Bhattacharyya; Diganta Kumar Das (Journal of Fluorescence, 2016)

Biotransformation of hexavalent chromium into extracellular chromium(III) oxide nanoparticles using Schwanniomyces occidentalis - Pallavi T. Mohite; Ameeta Ravi Kumar; Smita S. Zinjarde (Biotechnology Letters, 2016)

Evaluation of physiochemical factors affecting high-frequency plant regeneration of Blyttia spiralis (synonym: Pentatropis spiralis), a threatened climber of medicinal value - Ashok Kumar Patel; Deepika Lodha; Kheta Ram; Smita Shekhawat; Narpat S. Shekhawat (In Vitro Cellular & Developmental Biology - Plant, 2016)

Free radical-scavenging activities of Homalium species – An endangered medicinal plant of Eastern Ghats of India - Ajay Kumar Mahapatra; Sweta Smita Pani; Atish Kumar Sahoo (Natural Product Research, 2015)

A New Fluorescent “Off-On” Sensor for Al3+ Derived from L-alanine and Salicylaldehyde - Smita Sarma; Pradip Kr. Bhattacharyya; Diganta Kumar Das (Journal of Fluorescence, 2015)

Enhancing Degradation of Low Density Polyethylene Films by Curvularia lunata SG1 Using Particle Swarm Optimization Strategy - Sangeeta Raut; Smita Raut; Manisha Sharma; Chaitanya Srivastav; Basudam Adhikari; Sudip Kumar Sen (Indian Journal of Microbiology, 2015)

Early Eocene rodents (Mammalia) from the Subathu Formation of type area (Himachal Pradesh), NW sub-Himalaya, India: Palaeobiogeographic implications - Smita Gupta; Kishor Kumar (Journal of Earth System Science, 2015)

Biomarker System for Genetic Analysis of Stored Grain Pests Callosobruchus maculatus and Callosobruchus chinensis - Divya Pandey; Bharat Neekhra; Meeta Mishra; Smita Banerjee; Subodh Kumar Jain (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Yarrowia lipolytica NCIM 3589, a tropical marine yeast, degrades bromoalkanes by an initial hydrolytic dehalogenation step - Aakanksha Vatsal; Smita S. Zinjarde; Ameeta Ravi Kumar (Biodegradation, 2015)

Real-time PCR technique for detection of arecanut yellow leaf disease phytoplasma - Smita Nair; O. M. Roshna; V. P. Soumya; Vinayaka Hegde; M. Suresh Kumar; Ramaswamy Manimekalai; George V. Thomas (Australasian Plant Pathology, 2014)

Comparative QSAR and pharmacophore analysis for a series of 2,4-dihydro-3H-1,2,4-triazol-3-ones derivatives as angiotensin II AT1 receptor antagonists - Mukesh C. Sharma; Smita Sharma; Pratibha Sharma; Ashok Kumar; Kamlendra Singh Bhadoriya (Medicinal Chemistry Research, 2014)

Natural Products Modulate Eicosanoid Mediated Nodulation in Poekilocerus pictus Fab. (Acrididae, Orthoptera) - Ajay Pratap Singh; Manish Kumar Jain; Smita Banerjee (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

QSAR and pharmacophore approach on substituted imidazole derivatives as angiotensin II receptor antagonists - Mukesh C. Sharma; Smita Sharma; Pratibha Sharma; Ashok Kumar; Kamlendra Singh Bhadoriya (Medicinal Chemistry Research, 2014)

Pharmacophore and QSAR modeling of some structurally diverse azaaurones derivatives as anti-malarial activity - Mukesh C. Sharma; Smita Sharma; Pratibha Sharma; Ashok Kumar (Medicinal Chemistry Research, 2014)

Comparative QSAR and pharmacophore modeling of substituted 2-[2′-(dimethylamino) ethyl]-1, 2-dihydro-3H-dibenz[de,h]isoquinoline-1,3-diones derivatives as anti-tumor activity - Mukesh C. Sharma; Smita Sharma; Pratibha Sharma; Ashok Kumar (Medicinal Chemistry Research, 2013)

Molecular modeling and pharmacophore approach for structural requirements of some 2-substituted-1-naphthols derivatives as potent 5-lipoxygenase inhibitors - Mukesh C. Sharma; Smita Sharma; Pratibha Sharma; Ashok Kumar (Medicinal Chemistry Research, 2013)

Determination of Genetic Diversity of the Morinda tinctoria Population in Historical Mandore Garden - Smita Shekhawat; Sumitra Kumari Choudhary; Harish; Amit Kumar Gupta; Narpat Singh Shekhawat (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Differential Expression of Rice Lambda Class GST Gene Family Members During Plant Growth, Development, and in Response to Stress Conditions - Smita Kumar; Mehar Hasan Asif; Debasis Chakrabarty; Rudra Deo Tripathi; Rama Shanker Dubey; Prabodh Kumar Trivedi (Plant Molecular Biology Reporter, 2013)

Salicylaldehyde Phenylhydrazone: A New Highly Selective Fluorescent Lead (II) Probe - Diganta Kumar Das; Priyanka Goswami; Smita Sarma (Journal of Fluorescence, 2013)

An improved Agrobacterium-mediated transformation of recalcitrant indica rice (Oryza sativa L.) cultivars - Manju Shri; Arti Rai; Pankaj Kumar Verma; Prashant Misra; Sonali Dubey; Smita Kumar; Sikha Verma; Neelam Gautam; Rudra Deo Tripathi; Prabodh Kumar Trivedi; Debasis Chakrabarty (Protoplasma, 2013)

In silico analyses of superoxide dismutases (SODs) of rice (Oryza sativa L.) - Budheswar Dehury; Kishore Sarma; Ranjan Sarmah; Jagajjit Sahu; Smita Sahoo; Mousumi Sahu; Priyabrata Sen; Mahendra Kumar Modi; Gauri Dutta Sharma; Manabendra Dutta Choudhury; Madhumita Barooah (Journal of Plant Biochemistry and Biotechnology, 2013)

Enhanced production of vasicine in Adhatoda vasica (L.) Nees. cell culture by elicitation - Sweta Bhambhani; Vijai Singh Karwasara; Vinod Kumar Dixit; Smita Banerjee (Acta Physiologiae Plantarum, 2012)

Statistical medium optimization for enhanced azadirachtin production in hairy root culture of Azadirachta indica - Smita Srivastava; Ashok Kumar Srivastava (In Vitro Cellular & Developmental Biology - Plant, 2012)

Genome wide identification of Dof transcription factor gene family in sorghum and its comparative phylogenetic analysis with rice and Arabidopsis - Hariom Kushwaha; Shubhra Gupta; Vinay Kumar Singh; Smita Rastogi; Dinesh Yadav (Molecular Biology Reports, 2011)

Anti-biofilm potential of a glycolipid surfactant produced by a tropical marine strain of Serratia marcescens - Devendra H. Dusane; Vinay S. Pawar; Y. V. Nancharaiah; V. P. Venugopalan; Ameeta Ravi Kumar; Smita S. Zinjarde (Biofouling, 2011)

Differential expression and alternative splicing of rice sulphate transporter family members regulate sulphur status during plant growth, development and stress conditions - Smita Kumar; Mehar Hasan Asif; Debasis Chakrabarty; Rudra Deo Tripathi; Prabodh Kumar Trivedi (Functional & Integrative Genomics, 2011)

Cross-Species Induction of Antimicrobial Compounds, Biosurfactants and Quorum-Sensing Inhibitors in Tropical Marine Epibiotic Bacteria by Pathogens and Biofouling Microorganisms - Devendra H. Dusane; Pratiek Matkar; Valayam P. Venugopalan; Ameeta Ravi Kumar; Smita S. Zinjarde (Current Microbiology, 2011)

UDP-N-acetylglucosamine enolpyruvyl transferase from Pseudomonas aeruginosa - Smita Dube; Kamna Nanda; Reema Rani; Namrata Jit Kaur; Jatin Kumar Nagpal; Dilip J. Upadhyay; Ian A. Cliffe; Kulvinder Singh Saini; Kedar P. Purnapatre (World Journal of Microbiology and Biotechnology, 2010)

Aspartate aminotransferase is involved in cold adaptation in psychrophilic Pseudomonas syringae - V. R. Sundareswaran; Ashish Kumar Singh; Smita Dube; S. Shivaji (Archives of Microbiology, 2010)